Penegakan Hukum Pidana Internasional terhadap Kejahatan Perang dalam Konflik Rusia dan Ukraina Berdasarkan Statuta Roma 1998 - Amelia Suci Rahmadani; Dwi Putri Lestarika (Lembaga Yasin AlSys, 2026)
The armed conflict between Russia and Ukraine has given rise to various allegations of war crimes that have attracted the attention of the international community, particularly regarding the effectiveness of international criminal law enforcement. Although Russia is not a state party to the 1998 Rome Statute, the International Criminal Court (ICC) still has an important role in prosecuting perpetrators of international crimes. This study aims to analyze the application of ICC jurisdiction to alleged war crimes in the Russia–Ukraine conflict even though Russia is not a state party to the Rome Statute, as well as to identify the juridical and political challenges in the enforcement of international criminal law. This study employed a normative legal research method with statutory, conceptual, and case approaches. The results show that the ICC still has a basis for jurisdiction through the territorial principle based on Ukraine’s ad hoc declaration pursuant to Article 12(3) of the Rome Statute, as well as through the principle of complementarity, which places the ICC as the last resort when a state is unable or unwilling to enforce the law effectively. However, the implementation of such jurisdiction faces various challenges, including jurisdictional limitations over non-state parties, dependence on international cooperation, issues of immunity of state officials, global political dynamics, evidentiary constraints in situations of armed conflict, as well as the not yet optimal universalization of the Rome Statute. These findings indicate that the effectiveness of international criminal law enforcement in the Russia–Ukraine conflict depends not only on the ICC’s normative legitimacy, but also on political support and the commitment of the international community to preventing impunity for war crimes.